Reforms, Research and Variability:A Reply to Lois Weiner - Resnick, Lauren B. (Education Policy Analysis Archives, 2003)
Lois Weiner (2003) argues that the research reports from High Performance Learning Communities (HPLC) were biased because of the close working relationships between the researchers and the leaders of the Community School District Two (CSD2) reform. Contrary to any claims otherwise, this relationship was quite open and acknowledged. The intent of the HPLC investigation was always to link scholars and practitioners in a new form of research and development in which scholars became problem-solving partners with practitioners. There are important issues about how to profitably conduct such “problem-solving” research. These issues are worth substantial attention from the communities of researchers and practitioners as collaborative research/practice partnerships proliferate. Serious studies of such partnerships are needed, going well beyond the anecdotal attacks offered by Weiner in her article.